Anterior cruciate ligament reconstruction. Issue 1 (22nd January 2016) - Irarrázaval, Sebastián; Kurosaka, Masahiro; Cohen, Moises; Fu, Freddie H
Abstract : Anterior cruciate ligament (ACL) reconstruction is a common procedure performed by orthopaedic surgeons, particularly in association with sports-related injuries. Over the past 10 years, a renewed interest in the native anatomy of the ACL has facilitated a progression from non-anatomic to more anatomic reconstruction techniques. The anatomic and individualised ACL reconstruction concept attempts to closely reproduce the patient's individual anatomy with the goal of reproducing the native ACL characteristics and improving patient outcomes. Measurements of the patient's anatomy help determine graft choice and whether anatomic reconstruction should be performed with an single-bundle or double-bundle technique. The bony landmarks and insertions of the ACL are preserved to assist with anatomic placement of both tibial and femoral tunnels. Long-term outcomes for anatomic ACL reconstruction are unknown and future research, considering biomechanics and clinical outcomes, should be focused on this area. Future studies may yield important information with regard to the potential progression to osteoarthritis after ACL reconstruction, including factors affecting or preventing it. In this State of the art review, we have attempted to summarise the best available evidence addressing ACL injury diagnostics, treatment, surgical techniques, complications, tips, pitfalls and geographical differences, following our primary goal of improving medical care and outcomes for patients who suffer an ACL injury.